User Behavior of Technology Towards Digital Samsat Services Use Technology Acceptance Model and Theory of Planned Behavior - Rina Mudjiyanti; Arini Hidayah; Ani Kusbandiyah; Sri Wahyuni (Trescode Green Organization, 2024)
Digitalization of digital samsat applications such as Signal and NewSakpole, in this study the object is motor vehicle taxpayers in Banyumas Regency through the technology acceptance model and theory planned behavior approaches. This study aims to analyze the usefulness of digital applications for motor vehicle tax payments. The TAM and TPB models are frameworks for explaining the behavior of technology users towards digital samsat applications. The ease of using the digital Samsat application is expected to increase the effectiveness of the ease of tax payment transactions, compliance, and increase regional original income from the motor vehicle tax sector. This research is important to do because it has an impact on the ability to increase regional income from the PKB sector for one period or one year. The results of the study involving 108 respondents showed that the use of digital samsat applications is highly dependent on taxpayer behavior. Taxpayer behavior in this study was able to mediate the relationship between perceived usefulness and use of digital Samsat applications. This shows a change in the attitudes and behavior of taxpayers who increasingly require effectiveness and efficiency in the tax payment process. Taxpayer behavior has not been able to mediate the relationship between ease, security and quality in the use of digital Samsat applications. This can also be seen as an independent variable, taxpayer behavior does not affect the use of digital samsat applications. Perceptions of ease, security and quality of digital samsat have an influence on the use of digital PKB applications. While ease and benefits do not affect the digital samsat application.